ANALISIS KESULITAN GURU DALAM PENERAPAN PROJECT PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA MATERI PEMANFAATAN SAMPAH DI LINGKUNGAN SEKOLAH SDN 14 SADIA KOTA BIMA - hikmatul; Ahmadin; Aris Iwansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the difficulties of teachers in implementing the Pancasila student profile strengthening project (P5) on the material of waste utilization in the environment of SDN 14 Sadia, Bima City. The background of this study is based on the importance of implementing the Pancasila student profile strengthening project (P5) as an effort to analyze the difficulties of teachers, especially in terms of waste utilization in the school environment. This study uses a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews with teachers and students, and documentation. The results of the study indicate that the implementation of the Pancasila student profile strengthening project (P5) on the material of waste utilization in the environment of SDN 14 Sadia, Bima City can have a positive impact on knowing what difficulties teachers face and efforts to overcome them. So that both students and teachers can optimally utilize waste. The conclusion of this study shows that there are effective solutions to the difficulties of teachers in implementing the Pancasila student profile strengthening project (P5) in terms of utilizing waste in the school environment so that it can be used creatively, including schools need to organize training on Pancasila Student Project activities for teachers as a means of improving character education in students, adequate budget allocation is needed to provide facilities and infrastructure that support the success of project activities, provision of quality resources such as learning materials, learning media, and technological devices. In addition, teachers need to plan good time management, and teachers need to provide strong motivation and arouse students' interest in learning.